An Analysis Of Verbal Bullying On Students’ Interaction And It’s Impacts On The Students’ Learning Interest At Smp Negeri 1 Palibelo - Syarifuddin, Syarifuddin; Hendrawansyah, Hendrawansyah; Putra, Rio Adi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to investigate the types of verbal bullying by students in school and its impacts on students' learning interest. Descriptive qualitative method was applied to investigate the case. The data source were 23 students who are indicated to be victims of bullying from 40 participants. Data collection techniques through observation, questionnaires, and interviews. While the data analysis technique were classification, identification, analyzing, and drawing conclusion. The results showed that there were three types of verbal bullying that often appeared. The form were mocking, insulting, and name calling. Among those types, name calling was the most occurred type of verbal bullying with 60,9%, then following by mocking with 34,8%, and the last was 4,3% insulting. Furthermore, 57,5% students who became victims of verbal bullying claimed and admitted that they experienced the impact of verbal bullying. It was recorded that 52,2% of students lost their concentration in learning, 39.1% of students experienced a decrease interest in learning and 8,7% of students could not sleep well because of verbal bullying. Therefore, this research concluded that students at SMP Negeri 1 Palibelo experienced a decrease interest in learning due to verbal bullying.